ATR, a DNA Damage Signaling Kinase, Is Involved in Aluminum Response in Barley - Szurman-Zubrzycka, Miriam; Nawrot, Malgorzata; Jelonek, Janusz; Dziekanowski, Mariusz; Kwasniewska, Jolanta; Szarejko, Iwona (Frontiers in Plant Science, 2019)
ATR (Ataxia Telangiectasia and Rad-3 Related Protein) is a DNA damage signaling kinase required for monitoring of DNA integrity. Together with ATM and SOG1, it is a key player in transcriptional regulation of DDR (DNA Damage Response) genes in plants. In this study we describe the role of ATR in the DDR pathway in barley and the function of HvATR gene in the response to DNA damages induced by aluminum toxicity. Aluminum is the third most abundant element in the Earth’s crust. It becomes highly phytotoxic in acidic soils, which comprise more than 50% of arable lands worldwide. At low pH, Al is known to be a genotoxic agent causing DNA damage and cell cycle arrest. We present a barley mutants, hvatr.g and hvatr.i, developed by TILLING strategy. The hvatr.g mutant carries a G6054A missense mutation in ATR gene, leading to the substitution of a highly conserved amino acid in the protein (G1015S). The hvatr.g mutant showed the impaired DDR pathway. It accumulated DNA damages in nuclei of root meristem cells when grown in control conditions. The TUNEL analysis revealed that 60% of mutant nuclei possessed DNA nicks and breaks, whereas in the wild type only 2% of nuclei were TUNEL-positive. The high frequency of DNA damages did not lead to the inhibition of the cell cycle progression, but the mutant showed an increased number of cells in the G2/M phase. In response to treatments with different Al doses, the hvatr.g showed a high level of tolerance. The retention of root growth, which is the most evident symptom of Al toxicity, was not observed in the mutant, as it was in its parent variety. Furthermore, Al treatment increased the level of DNA damages but did not affect the mitotic activity and the cell cycle profile in the hvatr.g mutant. Similar phenotype was observed for hvatr.i mutant, carrying another missense mutation leading to G903E substitution in HvATR protein. Our results demonstrate that the impaired mechanism of DNA damage response may lead to aluminum tolerance. They shed a new light on the role of ATR-dependent DDR pathway in an agronomically important species.